(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to find out: 1) To find out the difference in the effect of interval training and fartlek training on VO2Max in the high and low motivation groups, 2) To find out the interaction between exercise and motivation on VO2Max, and 3) To find out which of interval training and fartlek training is more effective in increasing VO2Max. The population is extracurricular participants of the MA Syekh Yusuf futsal. The sample used was 20 people. The sampling technique is total sampling and the ordinal pairing group division system. Study results: (1) There was a significant difference in the influence of participants who had high and low motivation on VO2Max, (2) There was an interaction between exercise (interval training and fartlek training) and motivation (high and low) on VO2Max, (3) There is a significant difference in influence between interval training and fartlek training, interval training is more effective in increasing VO2Max. The conclusion that interval training has a greater influence than fartlek training on VO2Max futsal extracurricular participants of MA Syekh Yusuf.